2007
DOI: 10.1021/es0708013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in the Estrogenicity of a Sewage Treatment Plant Effluent and Its Biological Significance

Abstract: Daily variation in the estrogenic activity of effluent released by a modern sewage treatment plant (STP) was measured and its effects on the physiology, behavior, and reproductive success of male fish were evaluated. As measured by an estrogen receptor binding assay, the daily estrogenic activity of this effluent was both high and extremely variable (42 +/- 25.4 [mean +/- SD] ng 17beta-estradiol (E2) equivalents/L; n = 18). Liver VTG mRNA expression in male fathead minnows (FHM) covaried with the binding assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 37 publications
3
63
1
Order By: Relevance
“…Other factors including sampling time and individual water consumption are also very important. We collected samples between 9 and 11 o'clock; however, previous research has reported that highest estrogenic activities appeared at 10 o'clock in WWTP effluent from the USA (Martinović et al 2008). Chang et al (2011) reported a lower influent concentration of E1 and E2, which was determined according to 24 h composite samples.…”
Section: Levels Of Steroid Estrogens In Wwtp Influent and Effluentmentioning
confidence: 98%
“…Other factors including sampling time and individual water consumption are also very important. We collected samples between 9 and 11 o'clock; however, previous research has reported that highest estrogenic activities appeared at 10 o'clock in WWTP effluent from the USA (Martinović et al 2008). Chang et al (2011) reported a lower influent concentration of E1 and E2, which was determined according to 24 h composite samples.…”
Section: Levels Of Steroid Estrogens In Wwtp Influent and Effluentmentioning
confidence: 98%
“…After collection, all samples were stored in amber glass bottles into which 1% formaldehyde (v/v) was preadded to restrain the microbial activity and then taken back to the laboratory for analysis. The sampling time was set between 2:00 and 4:00 p.m. because the hourly fluctuation of the effluent estrogenicity was found to be insignificant on one sampling day except the morning period when a urine peak load usually appeared in the STP [17]. The samples were collected in four seasons on January 5 (winter), April 14 (spring), July 30 (summer) and November 3 (autumn) throughout 2009, corresponding to a wastewater temperature of 12, 19, 27 and 18°C, and a mixed liquor suspended solids (MLSS) concentration in the return sludge of 5.11, 6.70, 7.80 and 10.31 g/L, respectively.…”
Section: Sample Collection and Pretreatmentmentioning
confidence: 99%
“…However, exposure to exogenous steroidal estrogens and other estrogenic contaminants in the aquatic environment has the potential to disrupt fish development and reproduction [1][2][3]. Of particular concern is the ability of estrogens to feminize male fish through disruption of testis growth by development of oocytes and stimulation of vitellogenin production [4].…”
Section: Introductionmentioning
confidence: 99%
“…Effluents from wastewater treatment plants (WWTPs), in particular, have been shown to contain complex mixtures of endocrinedisrupting compounds [5][6][7][8], including steroidal estrogens such as 17b-estradiol (E2) and ethinylestradiol [6,[9][10][11], as well as plant-derived phytoestrogens [12]. Feminization of male fish exposed to estrogenic effluents has been widely documented, with a number of studies showing sufficient levels of estrogenic compounds to produce adverse effects on reproduction [1,3,6,13,14].…”
Section: Introductionmentioning
confidence: 99%